Policy Evaluation of the PKH Plus Programme in the Empowerment of Older Persons at the East Java Provincial Social Service - Tatok Subartak; Aris Sunarya; Amirul Mustofah (International Journal of Social Science and Humanity, 2026)
The government has launched various programmes to improve the welfare of older persons, yet social problems relating to them persist, making policy evaluation essential in order to assess whether such programmes achieve their intended goals. This study evaluates the PKH Plus social assistance programme for the empowerment of older persons at the East Java Provincial Social Service. Unlike previous studies that emphasise policy implementation, this research strengthens the policy evaluation perspective by applying William N. Dunn’s six evaluation criteria: effectiveness, efficiency, adequacy, equity, responsiveness and appropriateness. A qualitative descriptive method was used, with data collected through observation and interviews and analysed through data reduction, data presentation, and conclusion drawing or verification. The results show that PKH Plus has been fairly effective and appropriate in improving the welfare of older persons in recipient regencies and cities, and is responsive to beneficiaries’ needs through accompaniment, family capability meetings and the older persons’ integrated health post (Posyandu). However, the programme remains constrained in terms of efficiency, adequacy and equity owing to a limited budget sourced solely from the regional budget, human resources that are merged with the regular PKH, and uneven access to integrated health post services for older persons. The evaluation recommends the institutional separation of PKH Plus from the regular PKH, the expansion of the budget and beneficiary quotas, and broader, more equitable service coverage.